2022
DOI: 10.1037/apl0000750
|View full text |Cite
|
Sign up to set email alerts
|

I know how I feel but do I know how you feel? Investigating metaperceptions to advance relationship-based leadership approaches.

Abstract: Although Leader-Member Exchange (LMX) theory suggests that leaders and followers see their relationship similarly as a function of repeated role exchanges, empirical research has found only modest levels of agreement between leader and follower LMX ratings. This is not only problematic theoretically, it also brings up the question as to whether leader-follower dyad members are even aware of the lack of convergence of their relationship perceptions. To explore this issue, we draw from social psychology research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…This design could allow testing of whether the leader’s humility is relationship-specific and whether it is reciprocated by subordinates relationally. Such a study could follow the approach taken to examine agreement between leaders and followers on LMX ratings (Yuan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This design could allow testing of whether the leader’s humility is relationship-specific and whether it is reciprocated by subordinates relationally. Such a study could follow the approach taken to examine agreement between leaders and followers on LMX ratings (Yuan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Relationship-specific behaviors occur vertically and horizontally in organizations. For example, vertically, employees' perceptions of leader's behavior vary significantly from one subordinate to another (Yuan et al, 2022). Horizontally, coworkers' ratings of others' listening, speech quality, helping organizational citizenship behavior (Kluger et al, 2021), envy, contempt, and knowledge hiding (Li et al, 2022) show significant fluctuation from one coworker to another.…”
Section: Relational Self Theorymentioning
confidence: 99%
“…Specifically, the resources that leaders can bring to their dyadic relationship (e.g., developmental and mentoring opportunities) are arguably scarcer and more valuable than what followers can contribute through their work efforts (Wilson et al, 2010). Given the inherent power differentials between leaders and followers (Yuan et al, 2022), followers may be more sensitive to ambiguities in their relationships than are leaders. This distinction arises because followers' misinterpretation and miscalculation of their relationship with the leader may carry greater costs than are borne by leaders who mischaracterize these relationships.…”
Section: Lmx Agreement Moderating the Lmx-performance Relationshipsmentioning
confidence: 99%
“…Moreover, such an integration can expand the theoretical horizon of LMX inquiries. For example, Yuan et al (2022) incorporated the critical notion of metaperceptions (i.e., an individual's inference of how the other party in the dyad feels about their relationship, Laing et al, 1966) into LMX research. Their findings indicated that dyadic LMX metaperceptions were both biased and inaccurate, suggesting leaders and followers may not even know that they do not see eye to eye regarding their relationship.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Researchers started paying attention to this form of identification following Millward (1995) and Brewer and Gardner (1996) work wherein they found that employees seek to foster meaningful relations with their customers, as they are the most salient group they interact with regularly (Paunova and Li-Ying, 2022). Previous research in this area has been ignorant of the relational level bonds that an individual develops during his interaction at the workplace and defining himself in relation to others (Andersen and Chen, 2002;Sluss and Ashforth, 2007;Yuan et al, 2021). In particular, the role of relational identification between an employee and his customer remains neglected.…”
Section: Employee-customer Identificationmentioning
confidence: 99%